Evaluasi Penerapan 4F (Food, Feed, Fuel, Fertilizer) dan Pendapatan Usahatani Integrasi Jambu Mete dan Ternak di Kabupaten Sampang, Indonesia - Kusnul Kotimah; Dwi Ratna Hidayati; Nor Qomariyah (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2025)
Cashew integration farming in Sampang Regency holds promising potential, as the region is one of the main cashew-producing areas in East Java Province. However, high poverty levels also characterize Sampang, and there is a lack of research exploring the impact of integrated cashew farming systems on farmers' income. This study aims to identify the implementation of cashew integration farming and to examine the relationship between the implementation of the 4F concept (Food, Feed, Fuel, Fertilizer) and farmers' income in Sampang Regency. This research adopts a mixed-methods approach, combining both qualitative and quantitative techniques. Primary data were collected from September to December 2024 through observation, interviews, and questionnaires in Banyusokah Village, Ketapang Subdistrict of Sampang Regency. The study population comprised farmers practicing integrated cashew farming in the region. A purposive sampling technique was used to select 40 cashew farmers who also rear livestock as respondents. The variables examined in this study centred on cashew production activities contributing to income (fixed and variable costs, production volume, and market price), as well as integrated farming practices associated with the 4F framework. Data were analysed using descriptive quantitative methods (statistical analyses using frequency distributions), income analysis, and chi-square tests. The results indicate that cashew-livestock integration farming is mutually beneficial, particularly through the provision of animal feed and organic manure, as well as the production of food and fuel. Cashew farmers applied mainly 3F, and their average income was IDR 2.501.318. However, there is no significant relationship between the application of the 4F concept and the income levels of farmers engaged in cashew-livestock farming in Sampang Regency. Farmers need hands-on guidance to enhance the 4F (Food, Feed, Fuel, Fertilizer) in order to improve their income.